The Liminal Landscape: The Reception of Western Press Freedom in Late Imperial China - Guo, Yi (Javnost-The Public, 2019)
The concept of “freedom of the press” has been an essential conceptual tool used across disciplines which has enabled Chinese people to participate discursively in politics since the late nineteenth century. As an alien concept transplanted into China, the introduction and reception of this concept into the Chinese historical context reflects China’s encounter with the Enlightenment and the global discourse of transcultural knowledge transference in modern history. Adopting a historical approach, this article examines primary archival sources in an effort to understand the transcultural travelling of the Western concept of “freedom of the press” in modern China. It describes how the idea was introduced into late imperial China from European and Japanese origins. By contextualising the introduction and reception of this concept in Chinese history, this article further analyses the cultural factors that exerted influences on Chinese understandings and interpretations of this concept at the turn of the twentieth century. It also argues that the legacy of this liminal landscape continues to have an impact on China’s press freedom in the twentieth century and beyond.